Effects of Electromagnetic Radiation from Microwave Ovens on Workers' Health at Cafeterias in some Higher Educational Institutions in Palestine - Isra’ Ribhi Abu Hadbah (My University, 2014)
This study highlights the effects of electromagnetic radiation from microwave ovens on the health of the workers who are exposed to this radiation during their work at cafeterias in four higher educational institutions in Palestine. To achieve the aim of the study, the researcher focused on a sample that consists of 28 workers whose ages range between 20-55 years. Measurements of heart pulse rate, blood oxygen saturation, tympanic temperature, systolic and diastolic blood pressure were taken three times between (8:00-8:30) am and another three times at the same day after the end of their using of the microwave ovens at around 2:00 till 2:30 pm. The average of these measurements was taken. The study was carried out during December 2013 and January 2014. The researcher of this study focused on four higher education institutions in the northern part of Palestine. These higher educational institutions are An-Najah National University, the Arab American University, Hisham Hijawi College, and Palestine Technical University. The gathered data were subjected to statistical analysis. The results demonstrate that the average of the measured values of radiation leakage equals 46.126 mW/m2. The average values of radiation leakage are small compared with the standard value which equals 5×104 mW/m2 recorded by American National Standard Institute. It has been concluded that there is a correlation between radiation leakage from microwave ovens with oven's age, distance from oven, and the duration of use. Using measurable health parameters to detect the effect on workers' health reveals that there is a change in the measurable parameters, but that change remains in the normal human range. That is, there is no dangerous health effects of microwave radiation from microwave ovens used in the cafeterias of the university under study, which indicates adopting high security factors in designing modern microwave ovens.

ألقت هذه الدراسة الضوء على تأثير الإشعاع الكهرومغناطيسي من أفران المايكروويف على العمال الذين يتعرضون لهذه الأشعة خلال عملهم في المطاعم في بعض مؤسسات التعليم العالي في فلسطين. شملت عينة الدراسة 28 عاملا و تتراوح اعمارهم بين (20-55) سنة . أخذت قياسات معدل نبض القلب, ونسبة الاكسجين في الدم, ودرجة حرارة الجسم عن طريق الاذن, وضغط الدم الإنبساطي والإنقباضي ثلاث مرات من الساعة 8:00-8:30 صباحا وثلات مرات في نفس اليوم بعد إنتهاء إستخدام أفران المايكرويف من الساعة 2:00-2:30 مساءً. ثم تم أخذ معدل هذه القياسات. أجريت هذه الدراسة خلال شهري كانون الأول 2013 وكانون الثاني 2014. ركزت الدراسة على أربعة من مؤسسات التعليم العالي في الجزء الشمالي من فلسطين وشملت جامعة النجاح الوطنية, والجامعة العربية الأمريكية, و كلية هشام حجاوي, وجامعة فلسطين التقنية. تم تحليل البيانات إحصائيا حيث أظهرت النتائج أن معدل القيم المقاسة لتسرب الأشعة يساوي 46.126 ملي واط /م2 واعتبرت هذه القيمة ضمن القيم المعيارية. ولقد أُستنتج من هذه الدراسة وجود ارتباط ما بين تسرب الأشعة من أفران المايكروويف مع البعد عن الفرن, وفترة الإستخدام. ومن خلال إستخدام قياس العوامل الصحية لكشف التأثير الصحي على العمال, تبين أن هناك تغيراً ملحوظاً في المتغيرات المقاسة إلا أنها بقيت ضمن الحد الطبيعي المسموح به للإنسان. توصلت الدراسة إلى أنه ليس هناك مخاطر صحية للأشعة المتسربة من أفران المايكروويف المستخدمة في مطاعم بعض مؤسسات التعليم العالي التي شملتها هذه الدراسة وهذا يشير إلى إعتماد عوامل أمان إضافية في تصميم أفران المايكروويف الحديثة وإستخدامها.
أثار الإشعاع الكهرومغناطيسي من أفران المايكروويف على صحة العمال في مطاعم بعض مؤسسات التعليم العالي في فلسطين